Precision CMB measurements with long-duration stratospheric balloons: Activities in the Arctic - DE BERNARDIS, Paolo; MASI, Silvia (Proceedings of the International Astronomical Union, 2012)
We report on the activities preparing long duration stratospheric flights, suitable for CMB (Cosmic Microwave Background) measurements, in the Arctic region. We focus on pathfinder flights, and on two forthcoming experiments to be flown from Longyearbyen (Svalbard islands): the OLIMPO Sunyaev-Zeldovich spectrometer, and the Large-Scale Polarization Explorer (LSPE). Copyright © 2013 International Astronomical Union.